A Feira Tikuna em Tabatinga – AM: sujeitos, produtos e estratégias de comercialização - Silva, Maderly Soares da (Brasil, 2022)
The present work had as objective to analyze the process of commercialization of the products at Feira Tikuna in the municipality of Tabatinga – AM. Data collections were carried out for 7 months, between September 2021 and March 2022. Observations in the study environment and applied forms with the marketers and consumers. Information related to the work of the social subjects involved in themarketing process and the strategies used by them to sell agricultural products.It was found that the marketing of agricultural products at the Tikuna Fair in Tabatinga is performed permanently. It is made up of marketers and indigenous family farmers and non-indigenous to the region. The Umariaçu indigenous community is the one that most offers products for on-site commercialization, followed by other floodplain and upland communities belonging to to the same municipality and neighboring countries. Production, in general, has a dual purpose, self-consumption and sale. A variety of species offered by the family farmers and fairgrounds, totaling about 68 species of agricultural products classified into 6 categories. It was identified that agricultural products come from 12 communities. There are also products that are sold in the market that the vendors do not know about. Origin, mainly the so-called Peruvian products. Five were found strategies used to commercialize products from family farming of local communities. It was concluded that the Tikuna Fair supplies relatively regional agriculturalists the urban population of the municipality of Tabatinga, there are several subjects involved in the process and marketing strategies to guarantee the income of the marketers.